Polymer-Supported Siloxane Transfer Agents for Pd-Catalyzed Cross-Coupling Reactions - Nguyen, Minh H. (2013)
[Image: see text] The design, synthesis and validation of a ROMP polymer supporting siloxane transfer agents have been achieved that permit efficient palladium-catalyzed cross-coupling reactions. The solubility properties of the polymer not only facilitate product purification, but also recycling without significant loss of cross-coupling activity.